PENGARUH METODE BIOTEKNOLOGI FERMENTASI KOMBUCHA BUNGA TELANG (Clitoria ternatea L) SEBAGAI ANTIBAKTERI GRAM POSITIF DAN NEGATIF - Firman Rezaldi; Retna Yulrosly Ningtyas; Siska Dwi Anggraeni; Aris Ma’ruf; Nisa Siti Fatonah; Fernanda Desmak Pertiwi; Fitriyani Fitriyani; Lucky Dita A; Sumarlin US; M. Fariz Fadillah; Andri Imam Subekhi (Jurnal Biotek, 2021)
Butterfly pea flower kombucha is one of the probiotic fermented drinks produced through a consortium between bacteria and yeast. Telang flower decoction is the raw material in this study. This study aimed to determine the antibacterial activity of telang flower kombucha at various sugar concentrations. Concentrations of sugars used in making kombucha Butterfly pea flower include 20%, 30%, and 40% (w/v), each repeated three times. Positive control was kombucha made from black tea, while negative control was sterile distilled water. The well diffusion method is one of the methods in antibacterial testing by calculating the diameter of the inhibition zone. The fermented kombucha flower has broad-spectrum antibacterial activity, indicated by its inhibition against Staphylococcus aureus, Staphylococcus epidermidis, Pseudomonas aeruginosa, and Esherichia coli. Telang flower kombucha at 40% sugar concentration showed the highest antibacterial activity means it has a potential functional drink that supports health aspects.